Qualitative Analysis of a Modified Leslie-Gower Model with Gestation Delay - Sivasamy, R.; Nivethitha, K.; Maheswari, S. (Journal of Applied Nonlinear Dynamics, 2026)
This paper explores the qualitative analysis of a modified Leslie-Gower prey-predator model where the consumption rate of prey is by per capita predator according to Beddington-DeAngelis functional response. Moreover, time-lag $(τ)$ is established to exploit a gestation period of predations. The permanence analysis of the proposed system is investigated. We study the local stability of the non-delayed model at all possible equilibrium points. It is demonstrated that the given model experiences Hopf bifurcation about the interior equilibrium point with respect to delay $τ$. Thereafter the stability and direction of Hopf bifurcation are formulated through normal and center manifold theorems. The derived criteria are justified with the help of numerical simulations.